A companion to African philosophy - Wiredu, Kwasi (Malden, MA Blackwell Pub, 2006)
This volume, comprised of 42 newly commissioned and 5 adapted essays, provides comprehensive coverage of African philosophy, ranging across disciplines and throughout the ages. The essays encompass all the main branches of philosophy-logic, epistemology, metaphysics, aesthetics, ethics, religion, and politics, among others-as these have occupied the African mind in both communal and individual conceptions. A special feature of the volume is the historical dimension, including a substantial treatment of ancient African philosophy as encountered in ancient Egypt, an extended study of medieval North African thinkers, an enlightening discussions of pre-colonial African philosophy, and a history of African political thought in the nineteenth and twentieth centuries.
Includes bibliographical references Index.
Keywords: African Pilosophy